Cross-cultural management and bicultural identity integration : when does experience abroad lead to appropriate cultural switching? - Friedman, Ray (2013)
As the business world becomes more global many managers have spent significant time studying and working abroad. Does this overseas experience re-shape how managers think about the world? In this study we examined attribution patterns of Taiwanese managers who have studied and worked abroad. We found that managers who have been abroad switch their cultural orientation as a result of being shown Western or Chinese cultural icons, but this effect only occurs for those high in bicultural identity integration (BII). We confirmed that this effect occurs when “environmental” priming is used, and also confirmed that this effect is found when examining pay allocation decisions (a typical managerial issue) in addition to attribution patterns. These results point to the benefits of hiring internationally experienced managers, but also suggest that international experience may not be enough—companies need to also assess managers’ BII to know if foreign experience will truly translate into culturally appropriate cognitive flexibility.